1998
DOI: 10.1074/jbc.273.9.5174
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mouse Cyp1B1 Gene

Abstract: Transcriptional activation of the Cyp1B1 gene in rodents is stimulated by both polycyclic hydrocarbons and cAMP. The mouse Cyp1B1 gene structure contains three exons, of which the second nucleotide of exon 2 is the translation start site. Primer extension analysis identified a transcription start domain defining an exon 1 of 371 base pairs. The sequence 1.075 kilobases upstream of the transcription start site showed 11 xenobiotic-responsive elements (XRE) (T n GCGTG or GCGTG) that are putative aryl hydrocarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(38 citation statements)
references
References 56 publications
1
37
0
Order By: Relevance
“…These factors may act by binding to cis-acting regulatory regions and functioning as transcriptional enhancers or repressors directly or by interacting with DNA or DNA-binding proteins that modulate higher order chromatin structure. These studies also demonstrate that chromatin structure likely plays a major role in transcriptional regulation of the human CYP1B1 gene, as has been suggested for the mouse gene (29,30).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…These factors may act by binding to cis-acting regulatory regions and functioning as transcriptional enhancers or repressors directly or by interacting with DNA or DNA-binding proteins that modulate higher order chromatin structure. These studies also demonstrate that chromatin structure likely plays a major role in transcriptional regulation of the human CYP1B1 gene, as has been suggested for the mouse gene (29,30).…”
Section: Discussionmentioning
confidence: 64%
“…ARNT, on the other hand, is known to partner with other transcription factors and activate genes in an aryl hydrocarbon-independent manner (37,38). It has been shown that complexes other than AhR/ARNT bind in vitro to two of the analogous DREs in this region in the mouse Cyp1B1 gene in two different cell types (29,30). Therefore, because evidence suggests there may be a role for the DREs in constitutive gene expression, we analyzed the involvement of these elements in constitutive expression of the human CYP1B1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene structure is distinct from other mammalian P450s comprising only three exons and having a very long 3Ј untranslated region in exon 3 that results in a 5.2-kilobase (kb) mRNA (11,12). CYP1B1 has a pattern of expression that differs from the other two CYP1 family P450s; it is expressed constitutively in steroidogenic tissues like the adrenal, ovary, and testes and is inducible by adrenocorticotropin, cAMP, peptide hormones, and aryl hydrocarbon receptor ligands (4,8,10,13,14).…”
mentioning
confidence: 99%
“…The heterodimer binds to the xenobiotic response element (XRE) (12) and alters expression of genes controlled by enhancer XREs. XREs, with the conserved core sequences "GCGTG", are found in the promoter regions of several genes involved in the metabolism of xenobiotics, including cytochromes P-450 (CYP1A1, CYP1A2, and CYP1B1) (13)(14)(15)(16), and NAD(P)H-quinone oxidoreductase (17). Studies of the regulation of these genes, especially the regulation of CYP1A1, have provided a basis for understanding the mode of action of dioxin and related compounds (18,19).…”
mentioning
confidence: 99%